Peran Kepala Sekolah Sebagai Supervisor Dalam Implementasi Kurikulum Merdeka Belajar (Studi Kasus SMP Negeri 1 Pudak Ponorogo) - Endang Setyawati; Dian Pratiwi (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
The implementation of the curriculum in Indonesia adapts to the demands of an increasingly developing era with the aim that people get an equal, fair and developed education. During the covid-19 pandemic, the implementation of online learning based on the 2013 Curriculum caused learning lost caused by one-way learning where students rely on knowledge from the internet so that opportunities to gain knowledge are limited. Responding to this, the Ministry of Education, Culture, Research and Technology instructed the implementation of an independent learning curriculum thats providing free freedom for teachers and students in determining learning that suits school conditions. The role of the school principal as a supervisor is fundamental in implementing the independent learning curriculum in schools. This research aims to analyze 1) The principal's supervision approach in implementing the independent learning curriculum at SMP Negeri 1 Pudak Ponorogo, 2). The principal's supervision technique in implementing the independent learning curriculum at SMP Negeri 1 Pudak Ponorogo. 3) The results of the principal's supervision in the implementation of the independent learning curriculum at SMP Negeri 1 Pudak Ponorogo. This research uses a descriptive qualitative approach, with a case study method with data collection techniques namely interviews, documentation and observation. Data sources were obtained from interviews with the principal, deputy principal for curriculum, deputy principal for student affairs, deputy principal for infrastructure, educators (teachers) and students of SMP Negeri 1 Pudak. The results showed that the principal as a supervisor uses two approaches to learning supervision, namely the teacher-centered approach and the student-centered approach. The three supervisor approaches generally used by the principal of SMP Negeri 1 Pudak are direct approach, non-direct approach and collaborative approach. The techniques used by the principal are individual and group techniques. Supervision activities that are often carried out are class visits, consultations, meetings, workshops, training and seminars. The success of principal supervision in implementing an independent learning curriculum can be seen from the cooperation in seeking continuous improvement in the learning management system and school administration, as well as realizing a sense of kinship through intensive communication or a persuasive approach.